FORMULATION AND PHYSICAL QUALITY TESTING OF SOLID SOAP SANDALWOOD OIL (Santalum album L.) COMBINATION OF RAMBUSA LEAF EXTRACT (Passiflora foetida L.) AS AN ANTIBACTERIAL AGAINST Staphylococcus aureus (Universitas Muhammadiyah Yogyakarta, 2025)
The skin is highly susceptible to infections and other skin diseases, one of which is caused by Staphylococcus aureus bacteria. Staphylococcus aureus is a Gram-positive bacterium, with the skin surface as its natural habitat. Sandalwood and rambusa oils are plants known for their antibacterial activity. The objective of this study was to determine the characteristics and physical quality of solid soap formulations made from sandalwood oil combined with rambusa leaf extract to inhibit Staphylococcus aureus bacteria. The method used in this research is experimental. Antibacterial testing was conducted using the disc diffusion method. The results indicated that the addition of sandalwood oil and rambusa extract in solid soap formulations significantly enhanced antibacterial activity against Staphylococcus aureus, with very strong inhibition. Specifically, the diameter of the inhibition zone in formulation 2 with a 50% concentration averaged 23 mm, while formulation 3 at 50% concentration showed an average of 19.8 mm. At a 100% concentration, formulation 3 showed an average inhibition zone of 26.5 mm. Furthermore, physical quality tests of the solid soap preparations confirmed that the results met the quality standards for solid soap as regulated by the Indonesian National Standard (SNI).